Old wine in a new bottle: Subprime mortgage crisis - causes and donsequences - Michael Mah-Hui Lim (Levy Economics Institute of Bard College, 2008)
This paper seeks to explain the causes and consequences of the United States subprime mortgage crisis, and how this crisis has led to a generalized credit crunch in other financial sectors that ultimately affects the real economy. It postulates that, despite the recent financial innovations, the financial strategiesleveraging and financial risk mismatchingthat led to the present crisis are similar to those found in the United States savings-and-loan debacle of the late 1980s and in the Asian financial crisis of the late 1990s. However, these strategies are based on market innovations that have heightened, not reduced, systemic risks and financial instability. They are as the title implies: old wine in a new bottle. Going beyond these financial practices, the underlying structural causes of the crisis are located in the loose monetary policies of central banks, deregulation, and excess liquidity in financial markets that is a consequence of the kind of economic growth that produces various imbalancestrade imbalances, financial sector imbalances, and wealth and income inequality. The consequences of excessive risk, moral hazards, and rolling bubbles are discussed.
Keywords: F33; F55; 330; Subprime Mortgage Crisis; Credit Crunch; U.S. Housing Bubble; Collateralized Debt Obligations; Credit Default Swaps; Wealth and Income Inequality; Leveraged Buyout; Conduits; Mortgage-backed Securities; Current Account Imbalance; Credit Risks; Financial Innovation; Moral Hazard; New Monetarism